UNIT 3.26 Overview of Post Cohen‐Boyer Methods for Single Segment Cloning and for Multisegment DNA Assembly. Issue 1 (4th January 2016) - Sands, Bryan; Brent, Roger
Abstract : In 1973, Cohen and coworkers published a foundational paper describing the cloning of DNA fragments into plasmid vectors. In it, they used DNA segments made by digestion with restriction enzymes and joined these in vitro with DNA ligase. These methods established working recombinant DNA technology and enabled the immediate start of the biotechnology industry. Since then, "classical" recombinant DNA technology using restriction enzymes and DNA ligase has matured. At the same time, researchers have developed numerous ways to generate large, complex, multisegment DNA constructions that offer advantages over classical techniques. Here, we provide an overview of "post‐Cohen‐Boyer" techniques used for cloning single segments into vectors (T/A, Topo cloning, Gateway and Recombineering) and for multisegment DNA assembly (BioBricks, Golden Gate, Gibson, yeast homologous recombination in vivo, and ligase cycling reaction). We compare and contrast these methods and also discuss issues that researchers should consider before choosing a particular multisegment DNA assembly method. © 2016 by John Wiley & Sons, Inc.